Sasak Muslim Youth Marriage: The Unique Dowry Giving Phenomenon in Lombok Society - Muttaqin, Zainul; Tahir, Masnun; Bahtiar, M. Rifqi Subakti; Permana, Indra Martian (Cyber Media Indonesia, 2024)
The background of this research is the marriage of young Sasak Muslims in Lombok, Nusa Tenggara Bara, an important ritual that reflects the relationship between Islam and local culture. Many things are unique, primitive and controversial for some groups; an example is the practice of giving a unique dowry. This research methodology is descriptive qualitative. They are collecting data using observations and interviews regarding Islamic law practices, motivations, and views regarding providing unique dowries at the weddings of Sasak Muslim youth in East Lombok Regency. The results are 1) The practice of giving a unique dowry at the marriage of Sasak Muslim youth based on an agreement between both parties and occurs in three places in East Lombok Regency, namely: a) Mahar with Google Adsense in Sukadana Hamlet, Sukadana Village, Terara District, b) Mahar with grilled chicken in Pren Hamlet, Gunung Rajak Village, West Sakra District, c) Mahar with a cup of iron sand in Sukmulia Hamlet, East Pohgading Village, Pringgabaya District. 2) Giving a unique dowry is based on several motivations: a) Motivation of needs at that time. b) Social motivation or affiliation. c) Reward Motivation. d) Self-actualization motivation. e) Roja' and khauf motivation. 3) The unique dowry perspective of Islamic Law is permitted as long as it is not aimed at playing with marriage because, in Islam, there is no determination of the form, type and size of the dowry.